1975
DOI: 10.1139/b75-114
|View full text |Cite
|
Sign up to set email alerts
|

Study of callus growth and organ formation in wheat (Triticum aestivum) tissue cultures

Abstract: DUDITS, D., G. NEMET, and Z. HAYDU. 1975. Study of callus growth and organ formation In wheat (Triticlrtn aestii~rrtn) tissue cultures. Can. J. Bot.153: 957-963. Callus cultures of wheat (Tritic~rm aestivlrtn L.) were established by incubation of segments from root tips, shoots of seedlings, and from rachis with B5 and T media. 2,4,5-Trichlorophenoxyacetic acid, Benazolin, and Banvel D (Dicamba) were found to be appropriate growth regulators for initiation and maintenance of wheat callus cultures. Cytokinins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

1979
1979
1994
1994

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 3 publications
2
20
1
Order By: Relevance
“…An average of 20-25 regenerants were obtained per culture. Tile usefulness of Z and IAA in regeneration in cereal cultures has been reported by previous workers [2,4]. In triticale, 6% of the cultures gave rise to chlorophyll variants like striated and albino variants (Fig.…”
Section: Studies On Regeneration In Calhlssupporting
confidence: 62%
See 1 more Smart Citation
“…An average of 20-25 regenerants were obtained per culture. Tile usefulness of Z and IAA in regeneration in cereal cultures has been reported by previous workers [2,4]. In triticale, 6% of the cultures gave rise to chlorophyll variants like striated and albino variants (Fig.…”
Section: Studies On Regeneration In Calhlssupporting
confidence: 62%
“…The usefulness of 2,4-D as an effective auxin for caUus initiation and growth has been demonstrated for wheat [4,11], maize [5,6], barley [1] and triticale [13]. 2,4,5-T has been found to be very effective in caUus cultures of wheat [2]. Except in Sorghum [3], cytokinins have not proved necessary for initiation and maintenance of cereal cultures.…”
Section: Initiation Of Callus Cultures J)'om Immature Embryosmentioning
confidence: 99%
“…Shoots rarely have been redifferentiated from calluses derived from roots of germinating wheat (Shimada et al 1969). Dudits et al (1975) reported the regeneration of shoots and entire plantlets from rachis and shoot calluses of wheat, but the calluses failed to form shoots in subsequent subcultures.…”
Section: Discussionmentioning
confidence: 99%
“…With wheat (Triticum aestivum), only a very few plants have been obtained sporadically from wheat cultures derived from various organs (Shimada et al 1969;Dudits et al 1975). Stable, regenerated plants in wheat should be possible, since disease-resistant plants of maize (Gengenbach et al 1977) and potato (Matern et al 1978), and herbicide-resistant plants of tobacco (Chaleff and Parsons 1978) have been obtained by tissue culture techniques.…”
Section: Efficient Differentiationmentioning
confidence: 99%
“…Recently, using cultures derived from immature embryos of Pennisetum americanum, Vasil and Vasil [17] reported obtaining protoplasts capable of colony and plantlet formation. The second choice of explant is the immature inflorescence which has also been shown to produce shoot-forming cultures in Triticum [6,7], Sorghum [3], maize (P. Gordon, personal communication) and several temperate forage grasses [11 ]. There are also reports of plantlet formation from cultures of node origin in rye [16].…”
Section: Introductionmentioning
confidence: 99%